A Survey Student Behaviors Computer Security: Evidence from University - Palilingan, Verry Ronny; Rorong, Reski M; Yeremia, Undap E.B; Tambaani, Gerry T (International Journal of Information Technology and Education, 2022)
In lectures, of course, students definitely need a computer, whether it's to make assignments or to play games. Therefore, in using computers, students must maintain computer security from threats that can damage a system on a computer. The purpose of the study was to determine student behavior in maintaining computer security from existing threats. The results of the study were taken from a sample of students in the PTIK Department at UNIMA. The results of this study indicate that 91.3% of respondents stated that their computer system had an error and 8.7% of respondents stated that their computer system had never had an error.